Classical and Microwave-Assisted Synthesis of Substituted Dihydroxy-imidazolidine-2-thiones Compounds - Pıhtılı, Güzin; Tuncer, Hülya (My University, 2017)
In this study, N-N’-disubstitued thiourea and N-N’-disubstituted-4,5-dihydroxy-2-imidazolidine-2-thione were prepared through the reaction of suitable primary aromatic amines with phenylisothiocyanate and 4-methoxyphenylisothiocyanate. The synthesis of N-N’-disubstitued thiourea were carried out by classic methods. Later, the acid-catalyzed cyclocondensation in refluxing acetonitrile of aqueous glyoxal and led to the formation of the corresponding N,N’-disubstitued-4,5-dihydroxyimidazolidin-2-thiones. Thiourea derivatives were prepared both classical method and microwave assisted synthesis. Microwave-assisted reaction was performed in temperature and pressure control devices with the atmospheric pressure environment. The structures of synthesized organic compounds were characterized by FT-IR and 1 HNMR spectroscopy.
Keywords: Kimya; Uygulamalı; Kimya; Organik; Kimya; Tıbbi